2012
DOI: 10.1186/1479-5868-9-34
|View full text |Cite
|
Sign up to set email alerts
|

Levels of physical activity and sedentary time among 10- to 12-year-old boys and girls across 5 European countries using accelerometers: an observational study within the ENERGY-project

Abstract: BackgroundThe study aim was to objectively assess levels of sedentary time, light, moderate and vigorous physical activity (PA) among 10-12 year olds across five European countries and to examine differences in sedentary time and PA according to gender and country.Methods686 children (mean age = 11.6 ± 0.8 years, 53% girls, mean BMI = 19.0 ± 3.4 kg/m2) from Belgium, Greece, Hungary, the Netherlands and Switzerland wore Actigraph accelerometers and had at least 2 weekdays with minimum 10 h-wearing time and 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
178
2
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(219 citation statements)
references
References 41 publications
25
178
2
14
Order By: Relevance
“…Only one study also considered another model of accelerometer. 73 Using the same model of accelerometer may be perceived as facilitating the comparison between the studies, but the selected cut-off points Proportion of children engaged in sufficient PA…”
Section: Resultsmentioning
confidence: 99%
“…Only one study also considered another model of accelerometer. 73 Using the same model of accelerometer may be perceived as facilitating the comparison between the studies, but the selected cut-off points Proportion of children engaged in sufficient PA…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal analysis showed that activity level declined from 9 to 15 years (39). Due to various definitions of MVPA when assessed objectively, the prevalence of sufficiently active children and youth (6 to 15 years) varies from 99.6% to 0.4% in comparable studies (40)(41)(42)(43)(44)(45)(46). Using a similar definition as adopted in the Norwegian youth, Owen et al (46) suggested that 76% and 53% of 9-10 year old boys and girls, from a multi-ethnic district in England, met the recommended levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that boys are more physical active than girls (39,40,42,(44)(45)(46)(47), and that activity level declines with age (39)(40)(41)(42)47), also confirmed in longitudinal analysis (39,41). Children and youth from Norway, England and European countries spent between 376 and 576 minutes sedentary per day, when measured by accelerometry (39,(44)(45)(46). In the Norwegian sample this corresponds to approximately 50% of the day (when the monitor is worn) in 6 year olds, whereas sedentary time exceeded 70% of the day in 15 year olds.…”
Section: Introductionmentioning
confidence: 99%
“…Esto puede deberse al efecto dosis-respuesta (Martínez-Gómez et al, 2011). Esto significa, que generalmente las chicas son más sedentarias que los chicos (Verloigne et al, 2012), siendo por eso mayor el impacto logrado en chicas ante un mismo estímulo de ejercicio físico.…”
Section: Discusión Y Conclusiónunclassified